Investment Banking A Guide to Underwriting and Advisory Services - Iannotta, Giuliano; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The recent financial turmoil has raised suspects on investment banks and will certainly reshape the industry. However, the transactions traditionally managed by investment banks will still require the intervention of financial institutions, as always in the past. This book aims at providing an overview of these traditional investment banking activities. It covers the main areas of investment banking: security underwriting (equity and debt), syndicated loans, market for corporate control (M&As, LBOs, etc.), restructuring. There is an impressive amount of research papers on the different areas of investment banking. While this growing literature provides a conceptual framework, it has little to say on "how to do things". The aim of the book is to blend the scholars' and practitioners' views: every transaction is examined from both perspectives. Even when deeper attention is given to research, it is done with the simple and effective language of business.
to Investment Banking -- Private Equity -- Equity Offerings: Structure and Process -- Equity Offerings: Syndicate Structure and Functions -- Price Setting Mechanisms -- Debt Offerings -- Mergers and Acquisitions: Definitions, Process, and Analysis -- Risk Management in Mergers and Acquisitions -- Hostile Takeovers and Takeover Regulation -- Corporate Restructuring.
Keywords: Economics; Banks and banking; Economics/Management Science; Finance /Banking.